From a trickle to a potential torrent: crime and crime prevention as cascade phenomena - Kennedy, Jay P. (International journal of comparative and applied criminal justice, 2020)
This article reviews Braithwaite’s recent work Crime as a Cascade Phenomenon and offers insights into its potential to transform criminological theory and practice. In his article Braithwaite argues that the cascade phenomenon is useful to understanding the spread of crime prevention interventions across time and space. The cascade concept is used as a framework to discuss the macro-level factors that affect action and inaction at the community level. Through an incorporation of self-efficacy and collective efficacy within the cascade framework Braithwaite argues that individuals and communities are the mediums through which crime and crime prevention flow. These mediums are also important factors in the sustenance and proliferation of crime prevention cascades, particularly when those cascades include elements of reintegrative approaches to the destigmatisation of criminal histories. Cascades of crime prevention and non-violence reach their greatest potential when collective efficacy is used to create socially positive rather than exclusionary practices.